Dynamical characterization of the 6/1 mean motion resonance between Quaoar's ring and Weywot - Rodríguez, Adrián; Morgado, B. E.; Callegari, N. [UNESP] (Oxford University Press (OUP), 2023)
Recently, it has been reported the discovery of a dense ring around the trans-Neptunian object 50000 Quaoar. The ring particles seem to be very close to the 6/1 mean motion resonance with Weywot, the only known satellite in the system. In this work, we investigate the dynamical environment in the close vicinity of the 6/1 orbital resonance in the context of the restricted three-body problem. We aim to analyse whether, in view of observational constraints, the ring could be effectively evolving in resonant motion with the satellite. Through the technique of dynamical maps we identify and characterize the 6/1 mean motion resonance, finding that the main location of the resonance deviates by only 29 km from the central part of the ring. This difference lies within the 3σ confidence level, considering the uncertainties in the observational parameters. We also show that the Weywot's eccentricity plays a significant role in the dynamical structure of the 6/1 resonance. The results show that the resonance width is smaller than the estimated ring's width. Under assumption of a ring with eccentricity smaller than 0.05, clumping of test particles appears at the position of the different resonant multiplets, considering the nominal value of Weywot's eccentricity. This is in agreement with observations, which indicate that the estimated resonance width (≤10 km) is comparable with the narrow and dense arc of material within Quaoar's ring. Our results may be an indicative that the 6/1 resonance plays a key role in confining the arc ring.
Keywords: Planetary systems; planets and satellites: dynamical evolution and stability; planets and satellites: rings